Participatory Mentoring for Food Umkm: Integration of Digital Marketing and Simple Bookkeeping to Improve Local Food Security - Wapa, Andi; Wahyudi, Ade; Seran, Maria Virani; Putri, Nia Kartika; Alvy, Sahbana; Tobe, Marlin; Hakim, Arif Rahman; Khusna, Faza Amalia (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2026)
Local food UMKM have an important role in maintaining the availability and sustainability of a region's food supply. However, limitations in managing marketing and financial records are often an obstacle in increasing business competitiveness and resilience. This community service activity aims to increase the capacity of food UMKM through participatory assistance that integrates digital marketing and simple bookkeeping. The methods used are a qualitative approach including needs surveys, interactive training, hands-on practice, and evaluation of results. Digital marketing training focuses on utilizing social media to expand market reach, while simple bookkeeping is taught in direct writing. The participants of the activity amounted to 3 food UMKM actors in Kedungrejo Village, who were selected based on the criteria of active production and have the potential to develop. The results showed an increase in participants' knowledge related to digital marketing strategies by 80% and simple financial recording skills by 85% measured through descriptive data analysis based on the results of observation and skill achievements of participants after participating in the activity